2008
DOI: 10.1891/0889-8391.22.4.321
|View full text |Cite
|
Sign up to set email alerts
|

Interoceptive Exposure Exercises for Evoking Depersonalization and Derealization: A Pilot Study

Abstract: This study examined the potential of 11 interoceptive exposure exercises to produce depersonalization and derealization among high anxiety-sensitive undergraduate students. Inspired by a February 2007 thread on the Association for Behavioral and Cognitive Therapies listserv, we identified nine exercises and compared their capacity to produce depersonalization and derealization with two previously validated tasks: mirror and dot staring. Results indicated that five exercises, including hyperventilation (1 minut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 14 publications
0
25
0
Order By: Relevance
“…Instead, gazing at a fixed location in the room was left uncontrolled. In fact, previous studies found dissociation when observers were engaged in a task of dot-gazing (Miller et al, 1994;Leonard et al, 1999;Holmes et al, 2006;Lickel et al, 2008). Therefore, further research would be required to disentangle these different contributions made to dissociation in the control group.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Instead, gazing at a fixed location in the room was left uncontrolled. In fact, previous studies found dissociation when observers were engaged in a task of dot-gazing (Miller et al, 1994;Leonard et al, 1999;Holmes et al, 2006;Lickel et al, 2008). Therefore, further research would be required to disentangle these different contributions made to dissociation in the control group.…”
Section: Discussionmentioning
confidence: 95%
“…Firstly, in the control group, dissociation was almost surely under-evaluated, since control participants were not required to stare at a point in space (Lickel et al, 2008). Secondly, in the experimental group, the number of participants was quite limited; hence, a larger sample of individuals should have displayed a correlation between dissociation and strange-face illusions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The symptoms of DP/DR occur across a wide range of causes such as hypnosis (Wineburg & Straker, 1973), meditation (Castillo, 1990), hypnagogic and hypnopompic states (Lambert, Senior, Phillips, & David, 2000), sleep deprivation (Bliss, Clark, & West, 1959), sensory deprivation (Reed & Sedman, 1964), hyperventilation (Lickel, Nelson, Lickel, & Deacon, 2008), stress (Aderibigbe, Bloch, & Walker, 2001), and drug or alcohol use (Melges et al, 1974). The relatively high rates of reporting of these symptoms, in combination with the diverse range of precipitants, increase the need for clarification between normal and pathological episodes of DP/DR.…”
Section: Introductionmentioning
confidence: 99%
“…One reason for this may be the lack of a validated state depersonalization questionnaire, leading researchers to adapt preexisting trait measures of depersonalization for an in-the-moment timescale (e.g., Hoyer et al, 2013). There is conflicting evidence for a state co-occurrence of anxiety and depersonalization (Hoyer et al, 2013;Lickel et al, 2008;Sierra et al, 2002), so we tested all the hypothesized relationships on state levels of both anxiety and depersonalization. To increase variability in symptoms (which we expected to be too low and invariant at baseline for the statistical models), participants completed mild symptom induction tasks.…”
Section: State Effects Of the Symptom Inductionsmentioning
confidence: 99%